Feasibility of Endoscopic Thyroidectomy via Axilla and Breast Approaches for Larger Goiters: Widening the Horizons. (2nd October 2018) - Johri, Goonj; Chand, Gyan; Gupta, Nitish; Sonthineni, Chaitra; Mishra, Anjali; Agarwal, Gaurav; Mayilvaganan, Sabaretnam; Verma, Ashok Kumar; Mishra, Saroj Kanta
Abstract : Scarless (in the neck) endoscopic thyroidectomy (SET) has evolved into a cosmetically preferred alternative to conventional thyroidectomy (ConT). Recently many of our patients are demanding SET; however their goitres are larger than the recommended size of 4–6 cm. Our aim was to compare the outcomes of ET for small (<6 cm) vs large (≥6 cm) goitres and determine its feasibility in such cases. This is a retrospective analysis of prospectively maintained database of patients undergoing ET. Patients were divided into 2 groups: I, small (<6 cm) and II, large goitres (≥6 cm). Their demographic and clinicopathological profiles, operation time, conversion and complication rates, and hospital stay were compared. 99 patients (101 procedures) were included: group I, 60 patients (61 procedures), and group II, 39 patients (40 procedures). Mean tumor size (± SD) was 4.4 ± 0.9 cm and 6.7 ± 1.1 cm in groups I and II, respectively. The groups were comparable with respect to demographic and clinical profile except for mean duration of goiter [30.1 ± 32.6 months (group I) vs 60.5 ± 102.4 months (group I), p = 0.03] and gland weight [21.5 ± 15.3 grams (group I) vs 62.3 ± 51.3 grams (group II), p = 0.001]. Although there was no significant difference between mean operating times, long term perioperative outcomes, and conversion rates, temporary hypocalcaemia and length of stay were longer in group II. One patient had permanent vocal cord palsy (~1%, 1/101); none had permanent hypoparathyroidism. Our results indicate that ET can be offered to a subset of patients with larger goitres desirous of SET with no significant difference in mean operation time, conversions, and long term postoperative complications in experienced hands.